The Urgency of Educational Philosophy in Designing Meaningful Learning in Primary Schools - Nurbaiti, Nurbaiti; Ilahi, Afdhal (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Educational philosophy plays a crucial role in shaping the aims, processes, and quality of learning, particularly at the primary education level, which forms the foundation of students’ holistic development. However, previous studies indicate a persistent gap between philosophical discourse and its practical application in classroom learning. This study aims to examine the urgency of educational philosophy as a foundation for designing meaningful learning in primary education. Using a qualitative literature review approach, this study analyzes selected empirical and theoretical studies related to constructivism, humanism, and progressivism in primary school learning contexts.The findings reveal that these philosophical perspectives contribute significantly to the development of student-centered, contextual, and reflective learning designs. Constructivism supports active knowledge construction, humanism emphasizes emotional well-being and personal development, while progressivism promotes experiential and problem-based learning connected to real-life contexts. The analysis further shows that the integration of these philosophical principles aligns with the implementation of the Merdeka Curriculum, particularly in promoting differentiated instruction, project-based learning, and the development of the Pancasila Student Profile. However, the literature also indicates that limited philosophical literacy among teachers often results in procedural and administrative-oriented teaching practices. This study concludes that strengthening teachers’ understanding of educational philosophy is essential to ensure the effective design of meaningful learning in primary education. By grounding instructional practices in philosophical reflection, educational processes can move beyond administrative compliance toward more holistic and transformative learning experiences.